Adaptacion y calidad tecnologica de la variedad de frijol negro tacana - Lopez, E.=700 1 Becerra, N.; Cano, O.; Acosta, J.
(En, Es)
ilus., 22 ref.
Keywords: PHASEOLUS VULGARIS; RENDIMIENTO; ADAPTACION; ESTABILIDAD GENETICA; MEXICO; FRIJOL NEGRO TACANA